The Effect of Giving Rice Bran to Blood Glucose at Mice which Given Alloxan - Hapsari Sulistya Kusuma; JB Suparyatmo -; Bambang Suprapto (Universitas Muhammadiyah Semarang, 2016)
Abstract. World Health Organization predicts that Indonesia will encounter an increasing number of diabetic patients from 8.4 million in 2004 to approximately 21.3 million in 2030. The aims of this work is to investigate the effect of blood glucose following the administration of rice bran on the experimental rats treated with alloxan. This research is an experimental laboratory one with the randomized pre- and post-test research design with control group. The samples were white male Wistar rats aged seven weeks with the inclusion criteria, namely: blood glucose >142mg/dl, healthy, and energetic. They were divided into experiment and control groups. Each group had 6 rats. The total samples were 24. The t- test result shows that the difference of weekly blood glucose level of experiment groups and the one control group is statistically significant. It be concluded that the supplementation of rice bran powder amounting to 50% to the daily food intake of the diabetic rats exposed to the treatment can decrease their weekly blood glucose if compared to those that are not exposed to the same treatment.